2019
DOI: 10.1093/toxsci/kfz150
|View full text |Cite
|
Sign up to set email alerts
|

Atropselective Oxidation of 2,2′,3,3′,4,6′-Hexachlorobiphenyl (PCB 132) to Hydroxylated Metabolites by Human Liver Microsomes and Its Implications for PCB 132 Neurotoxicity

Abstract: Abstract Polychlorinated biphenyls (PCBs) have been associated with neurodevelopmental disorders. Several neurotoxic congeners display axial chirality and atropselectively affect cellular targets implicated in PCB neurotoxicity. Only limited information is available regarding the atropselective metabolism of these congeners in humans and their atropselective effects on neurotoxic outcomes. Here we investigate the hypothesis that the oxidation of 2,2′,3,3′,4,6′-he… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 91 publications
5
13
0
Order By: Relevance
“…The observation that PCB3 is oxidized in the meta or para position is consistent with studies demonstrating that higher chlorinated PCBs are preferentially oxidized in meta and para positions in studies with recombinant human cytochrome P450 enzymes or human liver microsomes. ,,,,, Similarly, the oxidation of PCB metabolites at the para or meta position is commonly observed in mammalian model systems, both in vitro and in vivo . ,,,, Studies with rats exposed to PCB3 through inhalation identified 3′-, 4′-, and 3-PCB3 sulfate isomers and 3′,4′-di-OH-3 conjugates. , Interestingly, rats receiving an intraperitoneal injection of PCB3 excreted 2′-, 3′-, and 4′-PCB3 sulfate in the urine, suggesting that ortho -hydroxylated PCB3 metabolites are formed in rats in vivo . 2′-OH-3, 3′-OH-3, and 4′-OH-3, together with two unidentified monohydroxylated metabolites, were observed in a metabolism study with rat liver microsomes .…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…The observation that PCB3 is oxidized in the meta or para position is consistent with studies demonstrating that higher chlorinated PCBs are preferentially oxidized in meta and para positions in studies with recombinant human cytochrome P450 enzymes or human liver microsomes. ,,,,, Similarly, the oxidation of PCB metabolites at the para or meta position is commonly observed in mammalian model systems, both in vitro and in vivo . ,,,, Studies with rats exposed to PCB3 through inhalation identified 3′-, 4′-, and 3-PCB3 sulfate isomers and 3′,4′-di-OH-3 conjugates. , Interestingly, rats receiving an intraperitoneal injection of PCB3 excreted 2′-, 3′-, and 4′-PCB3 sulfate in the urine, suggesting that ortho -hydroxylated PCB3 metabolites are formed in rats in vivo . 2′-OH-3, 3′-OH-3, and 4′-OH-3, together with two unidentified monohydroxylated metabolites, were observed in a metabolism study with rat liver microsomes .…”
Section: Resultssupporting
confidence: 71%
“…This observation suggests that HepG2 cells metabolize lower chlorinated PCBs in a congener-specific manner. Congener-specific differences in the metabolism of lower chlorinated PCBs have been documented for studies with purified rat cytochrome P450 enzymes, rat liver microsomes, or liver tissue slices from mice. , In-depth metabolism studies with lower chlorinated PCBs have not been reported for human model systems; however, higher chlorinated PCBs are metabolized in a congener-specific manner by human cytochrome P450 enzymes. ,,, …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolism studies with human liver microsome showed a depletion of (+)-PCB 91, 42 metabolism studies. 34,40,42,60 Consistent with this interpretation, we have demonstrated that the binding of PCB 136 atropisomers to rat cytochrome P450 enzymes 18 does not predict the atropselective metabolism of racemic PCB 136 by rat liver microsomes. 33 The results for the enantioselective analyses demonstrate that in vitro metabolism and toxicity studies with chiral compounds, including PCBs, should take their enantioselective partitioning into account.…”
Section: Resultssupporting
confidence: 53%
“…The faculty published 2 peer‐reviewed books, [ 238,239 ] 9 peer‐reviewed book chapters, [ 240–248 ] and 115 peer‐reviewed research papers. [ 249–363 ] This comes to 1.6 peer‐reviewed products/faculty/year during the 3‐year grant period, which is 3.2 times the rate of publication for natural science faculty at PUIs. [ 46 ]…”
Section: Research Accomplishments (Intellectual Merit) and Transformamentioning
confidence: 99%